(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
In the context of Ecuador’s economic and social development, the agricultural sector plays a fundamental role, and currently presents different challenges in terms of increasing productivity, so the purpose of this research is to analyze the factors that influence agricultural productivity in the northern area of the Province of Esmeraldas. It was conducted under the quantitative approach, with a descriptive type of research, the target population of the study were the producers of Eloy Alfaro Canton, located in Borbón, La Tola and other parishes, for which a sample of one hundred producers was considered. The data collection technique was the survey, whose instrument consists of a questionnaire with a Likert-type scale, the data were analyzed using descriptive statistics, with the calculation of the relative percentage frequency. As a result of the measurements made in terms of the economic dimension, it was found that most producers do not invest in crop maintenance and livestock activities, which results in risky production conditions; while, in the knowledge dimension, producers do not invest in maintenance or in innovation and technology, do not know processes and techniques to develop agricultural activities, do not have the organization and control of the processes they carry out, and therefore require training and technical assistance to increase productivity and be competitive in the market.